ANALYSIS OF TOTAL OIL CONSENTRATION IN THE WATERS OF PELINTUNG INDUSTRIAL AREA - Riska Khaironisa; Irvina Nurrachmi; Syahril Nedi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
AbstractThis research was conducted in July 2020 in Pelintung Dumai Waters. The purpose of this study was to determine the total oil concentration in the waters of the Pelintung Industrial Area. The method used is a survey method which is conducted at 4 stations. Total oil concentration samples were analyzed by gravimetric method. Based on the results of the study, the highest oil concentration was in the Pelintung Industrial Area waters (station III), namely 0.3245 ppm and the lowest concentration was in the mangrove forest area (station IV), namely 0.0738 ppm. The results of the Anova test carried out on the total oil concentration value between research stations obtained p value (0.019) <0.05. This shows that the total oil concentration between research stations is different.Keywords: Pelintung Village, Oil